Performa Emiten LQ45 Setelah Corporate Action (Right Issue: HMTED) - Hengkyap Jimmy Repi; Failur Rahman; Haerul Anam; Yohan Yohan; Rita Suirlan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Companies listed on the Indonesian Stock Exchange often expand, pay off debt, or increase capital in the form of corporations (Corporate Action). Even companies on the LQ45 list also carry out corporate actions. So, the aim of this research is to determine the issuer's performance after carrying out a rights issue. This research uses quantitative research and descriptive analysis methods. The population in this research is the LQ45 company that carried out a rights issue, with a sample of 5 companies, testing the hypothesis using the paired sample t-test. The data collection method in this research is documentation. The data collected is a type of secondary data sourced from company documentation in the form of annual reports. The results of this research show that there is no influence of the rights issue policy on share prices with a significance value of 0.844.